Analysis Digital Platform Factors of Use in the Implementation of Learning for High School Teachers in Tomohon City - Tiwow, Gilly Marlya; Rawis, Joulanda A.M.; Lengkong, Jeffry Sony Junus; Tambingon, Henny Nikolin; Umbase, Ruth; Palilingan, Rolles N.; Tamboto, Hendry; Evinita, Lenny Leorina (JR Education, 2025)
This study analyzes the factors influencing the use of digital platforms in teaching by high school teachers in Tomohon City, focusing on two main variables: performance expectations and effort expectations on usage behavior. The research background rests on the digital transformation process in education and the Independent Curriculum policy, which encourages the use of the Merdeka Mengajar Platform as a national digital learning ecosystem. The research method used a quantitative approach with Partial Least Squares (PLS) analysis to examine the relationships between variables. The sample consisted of high school teachers in Tomohon City who were both active and passive users of digital learning platforms. The results showed that performance expectations significantly influenced usage intentions and behavior, indicating that the perceived usefulness of the platform was the primary driver of its utilization. Effort expectations also significantly influenced usage intentions, but their influence on usage behavior was relatively lower than that of performance expectations. These findings emphasize the importance of designing systems that are easy to use while simultaneously providing tangible performance-added value for teachers. In conclusion, the successful implementation of digital platforms in high schools is strongly influenced by teachers' perceptions of usability and ease of use. Practical implications of this study emphasize the need for strengthened training, simplified digital administrative burdens, and improved technical support to optimize platform utilization.